NANOCOMPÓSITOS DE POLIPROPILENO E MONTMORILONITA: EFEITO DE MÚLTIPLAS EXTRUSÕES E DIFERENTES MASSAS MOLARES - Lima, Carlos Alberto Silva de (2014)
Nowadays, polymeric nanocomposites are well established in terms of their importance. However, there is still a long way to be investigated, since its methods for obtaining, processing and characterization, as there are many variables to be changed to optimize the responses. There is need in understanding the behavior of such materials when subjected to degradative processes, such as nanoparticles influence responses, and maximize or minimize the occurrence of these effects. In this work the behavior of neat polypropylene, polypropylene with organically modified montmorillonite, with and without the presence of a coupling agent (polypropylene-graft-maleic anhydride) when subjected to reprocessing in a twin screw extruder. It was investigated the effect of molar mass of the polypropylene matrix. For this purpose, three types of polypropylenes (high, middle and low molar mass) were processed one, or up to five times. Compositions were prepared neat or with 5% by weight montmorillonite, with and without the presence of coupling agent in the ratio 3:1. The properties is going to be investigated by the techniques of X-ray diffraction, scanning electron microscopy, rheology, infrared spectroscopy by Fourier transform, thermogravimetry, differential scanning calorimetry, tests of Izod impact and colorimetry. First of all, it was proved the presence of iron in the nanoclay, which affects the color of the sample due to oxidation of the iron cation. It was found that the samples became darker, redder, and more yellow because of the presence of the nanoparticles, iron and degradation. These results agreed with the changes observed by infrared spectroscopy, which generally showed low occurrence of the degradation rates of carbonyl and unsaturation, concluding that the greatest degradation occurred by the reduction in molar mass due to the β -scission process, confirming the reduction the values of complex viscosity. It was possible to monitor via rheology by different modes narrowing of the distribution of molar masses and the reduction in molar mass. Along with this information the values and behaviors of the slopes of the curves allowed us to infer the possible microstructure formed state of dispersion and distribution. XRD results indicated the formation of only a sample with an increase in the interlayer spacing, while the rheological results suggest that there is more than one sample with intercalated structure. Thus, there was a little difficulty using just one technique among them to state what actually occurred, concluding that it is essential to perform the technique of transmission electron microscopy. Addition of MMT and MMT / PP - g-MA afforded more thermally stable samples compared to pure PP, this was attributed to the effect of labyrinth. Finally, the impact resistance by the addition of montmorillonite was greater, it means that the clay did not act as stress concentrators, but as energy absorbers and hindered propagation of microcracks. But with PP-g-MA had a fracture behavior intermediate between PP and PP/MMT, with intermediate values of impact resistance. The fracture analysis was possible via SEM and allows to observe the morphology of the different samples.